Program wyborczy PRON 1984 r. [ulotka] . PRON 1984 electoral program. Flier - Komitet Oporu Społecznego (KOS). (Komitet Oporu Społecznego, 1984)
Red print on white paper. With a note handwritten on the back: "printed by KOS (Warszawa)". Flier, calling for boycott of the 1984 elections, contains a graphic image which represents a rationing coupon.